PENGARUH PENGETAHUAN KESEHATAN DAN BAHAYA JUNKFOOD DALAM PENGAMBILAN KEPUTUSAN MEMBELI PADA REMAJA DI RW 05 KECAMATAN JAMBE KABUPATEN TANGERANG TAHUN 2020 - Maharani, Siti; Imanuddin, Bayu (Nusantara Hasana Journal, 2022)
The purpose of this research is to find out whether or not the influence of health knowledge and the dangers of junkfood in making buying decisions for adolescents in RW 05, Jambe sub-district, Tangerang. This research was conducted in November 2019- July 2020 in RW 05 Jambe sub-district, Tangerang district. The method used in this study is quantitative, adolescent population in RW 05 Jambe sub-district Tangerang district. researchers took a sample of respondents as many as 75 respondents. Using univariate and bivariate analysis. Based on the t-test, 75 respondents obtained the health knowledge variable of (2,251) and the significance of (0.027) and the junkfood hazard variable obtained a result of (3,550) and the significance result of (0.001) in the F test results obtained for (11,293) this shows that the first variable is health knowledge and the second variable is junkfood hazard influences and significance in buying decision making.